Spatial, temporal and technical variability in the diversity of prokaryotes and fungi in agricultural soils - Jeanne, Thomas; D’Astous-Pagé, Joël; Hogue, Richard (Frontiers in Soil Science, 2022)
Several studies have shown that Illumina MiSeq high-throughput sequencing can be used to measure the diversity of prokaryotes and fungal communities that provide ecosystem functions in agricultural soils. Pedoclimatic properties of soils, together with cropping systems and agricultural management practices, are major drivers of soil microbiome diversity. Their effects must be quantified and compared to technical variability to improve the relevance of observed effects and the indicators that may result from them. This study was conducted: 1) To assess the effects of three sources of technical variability on the soil prokaryotes and fungal diversity; 2) To identify a source of technical variability that can be used as a threshold to better assess crop management effects; 3) To evaluate the effects of spatial and temporal variability compare to a technical threshold in three crop management contexts, potato, corn/soybean and grassland. Technical variability was evaluated in a basis of sampling, soil DNA extraction and amplicon sequencing source of variability. Spatial variability was evaluated using composite bulk soil cores at four sampling points covering 2500 m² per field. Geolocated soils were also collected on three sampling dates during the growing season to evaluate temporal variability. A technical variability threshold was determined for the soil DNA extraction variability with a delta of Shannon index of 0.142 and 0.390 and a weighted UniFrac distance of 0.081 and 0.364 for prokaryotes and fungi, respectively. We observed that technical variability was consistently similar or lower than the spatial and temporal variabilities in each of the microbial communities. Observed variability was greater for the diversity of fungi and the crop system has a strong effect on temporal and spatial variability.